2018
DOI: 10.1175/jhm-d-17-0106.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Correction of High-Mountain Precipitation Data Based on Glacio-Hydrological Modeling in the Tarim River Headwaters (High Asia)

Abstract: Mountain precipitation is often strongly underestimated as observations are scarce, biased toward lower-lying locations and prone to wind-induced undercatch, while topographical heterogeneity is large. This presents serious challenges to hydrological modeling for water resource management and climate change impact assessments in mountainous regions of the world, where a large population depends on water supply from the mountains. The headwaters of the Tarim River, covering four remote and highly glacierized As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 86 publications
6
49
0
Order By: Relevance
“…In most of the catchments, precipitation increased up to a certain elevation and then decreased. A similar altitudinal distribution of precipitation has been described in glacierized regions by Immerzeel et al () and Wortmann et al (). Glacier area, meltwater, and total runoff have their maxima around the middle altitudes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In most of the catchments, precipitation increased up to a certain elevation and then decreased. A similar altitudinal distribution of precipitation has been described in glacierized regions by Immerzeel et al () and Wortmann et al (). Glacier area, meltwater, and total runoff have their maxima around the middle altitudes.…”
Section: Discussionsupporting
confidence: 85%
“…Five datasets were compared and then selected APHRODITE precipitation and PGMFD temperature data to force the model. It is argued that APHRODITE precipitation is underestimated at higher elevations and needs to be corrected (Immerzeel et al ; Wortmann et al ). In this study, precipitation dataset was used without correction; however, precipitation lapse rates were derived using mass balance data at higher elevations to overcome the uncertainties in gridded precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…APHRODITE-2 shows the minimum snowfall across all products, and the differences between APHRODITE-2 and other products are most apparent in the two southern tiles (27 snowfall biases shown in Figure 7. Our results suggest that snowfall at these high-altitude tiles is generally underestimated in the gauge-based products over HMA, which is consistent with Immerzeel et al (2015) and Wortmann et al (2018), where high-altitude precipitation was found to be underestimated in many existing products. Since the gauge-based products derive their estimates primarily by interpolating rain-gauges located at lower elevations, it is possible that those gauges undercatch precipitation and do not capture orographic effects, which consequently underestimates snowfall.…”
Section: Annual Snowfall Time Series Among Different Productssupporting
confidence: 84%
“…Immerzeel et al (2015) showed, by inversely inferring precipitation from glacier mass balance, that high-elevation precipitation in the upper Indus basin is underestimated in APHRODITE, ERA-Interim, and TRMM, where ERA-Interim is a global atmospheric reanalysis from the European Centre for Medium-Range Weather Forecasts (ECMWF; Dee et al, 2011). Similarly, through evaluating runoff from glacio-hydrological modeling against observations, Wortmann et al (2018) showed APHRODITE underestimates precipitation by a factor of 1.5-4.4 in Tarim headwater catchments. The information gleaned from these previous studies generally provides bulk bias estimates through inferring precipitation from spatially integrated variables like streamflow or glacier mass balance.…”
Section: Introductionmentioning
confidence: 99%
“…gridded datasets over elevational profile may have been caused by the dynamic climatic system (Pang et al, 2014), precipitation dependency on altitude (Immerzeel et al, 2015;Wortmann et al, 2018) and the approaches used to generate these datasets (Harris et al, 2014;Huffman et al, 2010;Saha et al, 2010). The reason for the better representation of OBS climatology by the APHRO dataset is the use of observed data in its generation; however, the precipitation at ungauged elevation ranges is not extrapolated in APHRO dataset (Ji et al, 2020;Yatagai et al, 2012), which would affect its application in mountain glacierized catchments.…”
Section: Ability To Diagnose the Problems In Representing Climatologymentioning
confidence: 99%